Harmonic chess movement from cartoon character in ceramic art ware / Dr. Ing Oskar Hasdinor Hassan, Rusmadiah Anwar and Nurul Atiqah Ahmad - Hassan, Oskar Hasdinor; Anwar, Rusmadiah; Ahmad, Nurul Atiqah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
This innovation is an attempt to introduce a fresh concept to the environmental art by combining few elements of art with a modern concept design using ceramic materials. The objective of this innovation is to produce a set of ceramic art ware using chess concept by anticipating cartoon characters that lead to harmonica movement. A thorough designing process was done to finalize the concept and followed by a typical ceramic manufacturing process that lead to the final product. Finally the harmonic chess movement from cartoon character using ceramics was successfully produced. Art Ware